Menstrual hygiene practice among adolescent girls in Ethiopia: A systematic review and meta-analysis - Sahiledengle, Biniyam; Atlaw, Daniel; Kumie, Abera; Tekalegn, Yohannes; Woldeyohannes, Demelash; Agho, Kingsley Emwinyore (PLOS ONE, 2022)
Background Adolescent girls face several challenges relating to menstruation and its proper management. Lack of adequate sanitary products, inadequate water supply, and privacy for changing sanitary pads continue to leave adolescent girls with limited options for safe and proper menstrual hygiene in many low-income settings, including Ethiopia. These situations are also compounded by societal myths, stigmas surrounding menstruation, and discriminatory social norms. This systematic review and meta-analysis aimed to estimate the pooled proportion of safe menstrual hygiene management among adolescent girls in Ethiopia using the available studies. Methods We searched PubMed, Google Scholar, African Journal Online (AJOL), Hinari, Science Direct, ProQuest, Direct of Open Access Journals, POPLINE, and Cochrane Library database inception to May 31, 2021. Studies reporting the proportion of menstrual hygiene management among adolescent girls in Ethiopia were considered. The Cochrane Q test statistics and I2 tests were used to assess the heterogeneity of the included studies. Since the included studies revealed considerable heterogeneity, a random effect meta-analysis model was used to estimate the pooled proportion of menstrual hygiene management (MHM). Results Of 1,045 identified articles, 22 studies were eligible for analysis (n = 12,330 participants). The pooled proportion (PP) of safe MHM in Ethiopia was 52.69% (95%CI: 44.16, 61.22). The use of commercial menstrual absorbents was common 64.63% (95%CI: 55.32, 73.93, I2 99.2%) followed by homemade cloth 53.03% (95%CI: 22.29, 83.77, I2 99.2%). Disposal of absorbent material into the latrine was the most common practice in Ethiopia 62.18% (95%CI: 52.87, 71.49, I2 98.7%). One in four girls reported missing one or more school days during menstruation (PP: 32.03%, 95%CI: 22.65%, 41.40%, I2 98.2%). Conclusion This study revealed that only half of the adolescent girls in Ethiopia had safe MHM practices. To ensure that girls in Ethiopia can manage menstruation hygienically and with dignity, strong gender-specific water, sanitation, and hygiene (WASH) facilities along with strong awareness creation activities at every level are needed.